A method for detecting the content of thioester antioxidants
Through liquid chromatography technology and evaporative light scattering detector, combined with the extraction methods of cyclohexane, ethanol and copper acetate, the problem of detection of macromolecular thioester antioxidants is solved, and the detection effect of high accuracy and high sensitivity is achieved. The dissolution of polymers is avoided and the life of the detection equipment is extended.
Patent Information
- Application Number
- CN202310100098.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-02-11
AI Technical Summary
The prior art is difficult to systematically detect the content of macromolecular thioester antioxidants, mainly due to their strong extraction properties and poor UV absorption response, and lack of effective detection methods.
Liquid chromatography combined with evaporative light scattering detector, cyclohexane and ethanol are used as extraction solvents, and silver acetate is added to improve the dissolution rate and detection accuracy of thioester antioxidants, and the extraction conditions are controlled to avoid polymers. The use of copper acetate promotes the adsorption and dissolution of sulfur elements, optimizes the mobile phase and detection conditions to improve detection sensitivity and accuracy.
It improves the detection accuracy and sensitivity of macromolecular thioester antioxidants, reduces the dissolution of polymers, extends the service life of the chromatographic column, and ensures the accuracy and reliability of the detection results.
Smart Images

Figure CN115980241B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of antioxidant detection, and in particular to a method for detecting the content of thioester antioxidants. Background Art
[0002] As one of the important varieties of antioxidants, thioester antioxidants have the characteristics of high antioxidant efficiency, low volatility, and good oxidation resistance and coloring performance. They are mainly used in the processing and long-term thermal stability of styrene polymers such as HIPS, ABS, MBS, POM, PP, PUR, PVC and thermoplastic polyesters. In the PVC polymerization process, it can be used as an effective chain terminator and can be added to the monomers of polystyrene and PVC without affecting the polymerization reaction. Thioester antioxidants contain thioether structures, and their antioxidant mechanism is mainly to terminate the oxidation process of polymer materials by decomposing hydroperoxides through thioether structures. Thioester antioxidants include traditional small-molecule thioesters (such as antioxidant 300) and large-molecule thioesters (such as pentaerythritol tetra (3-dodecylthiopropionate)); small-molecule thioester antioxidants are easy to volatilize and migrate, and their application in specific materials or fields is limited. Large-molecule thioester antioxidants are not easy to volatilize and are difficult to migrate, and have attracted much attention in recent years. Currently, the macromolecular thioester antioxidants on the market mainly include the following:
[0003]
[0004] However, these thioesters with larger molecular weight are highly resistant to solvent extraction and are difficult to extract from polymer materials. Moreover, they mainly contain straight-chain alkanes and have poor ultraviolet absorption response. Therefore, there is currently no relatively systematic method for detecting their content. Summary of the invention
[0005] In order to establish a detection method for macromolecular thioester antioxidants, the present application provides a method for detecting the content of thioester antioxidants.
[0006] A method for detecting the content of thioester antioxidants, using the following technical scheme:
[0007] A method for detecting the content of a thioester antioxidant comprises the following steps:
[0008] S1. Sample pretreatment: crush the sample to be tested and extract it to obtain the sample solution to be tested;
[0009] S2. Prepare standard solution: prepare a standard solution of thioester antioxidant, the solvent in the standard solution needs to be the same as the solvent used to extract the sample in step S1;
[0010] S3, testing: the standard solution in step S2 is sequentially subjected to liquid chromatography testing to obtain a standard curve, and then the sample solution to be tested in step S1 is subjected to liquid chromatography testing, and the corresponding concentration is calculated according to the test results and the standard curve; the liquid chromatography uses an evaporative light scattering detector.
[0011] By adopting the above technical solution, the macromolecular thioester antioxidant has weak absorption in the ultraviolet region, so an evaporative light scattering detector is used in this application, which does not require a chromophore and can detect any sample with a volatility lower than that of the mobile phase. Although the macromolecular thioester antioxidant in this application has weak ultraviolet absorption, it has a high boiling point and good thermal stability. The use of an evaporative light scattering detector can greatly improve the accuracy of the detection of thioester antioxidants. In addition, the auxiliary carrier gas in the evaporative light scattering detector improves the detection sensitivity, keeps the detection cell clean, and avoids pollution; its high-precision atomization and evaporation temperature control ensure high-precision detection; further, compared with the commonly used differential refractive index detector, its baseline is more stable and the sensitivity is higher.
[0012] Preferably, in step S1, the sample to be tested is a polyolefin product containing antioxidant 412s or antioxidant DSTP.
[0013] Preferably, in step S1, the specific steps of extraction are: accurately weighing the crushed sample to be tested, adding it to a mixed solvent consisting of cyclohexane and ethanol, adding copper acetate to the solvent, performing heating and ultrasonic extraction, and after the extraction is completed, centrifuging and absorbing the supernatant as the sample solution to be tested.
[0014] By adopting the above technical scheme, in the present application, cyclohexane and ethanol are used as mixed extraction solvents during extraction. Cyclohexane has strong solubility for high molecular weight thioester antioxidants, which can promote their dissolution. At the same time, it also has certain solubility for many high molecular weight polymers. Although it can promote the dissolution of antioxidants, it will also introduce high molecular weight substances into the extract. Therefore, ethanol is added in the present application, which has poor solubility for most high molecular weight polymers and can reduce the dissolution of high molecular weight substances. Copper acetate is also added in the present application. Copper ions have a strong adsorption effect on sulfur elements in thioesters, so the introduction of copper ions into the solvent can promote the dissolution of high molecular weight thioester antioxidants.
[0015] Preferably, the volume ratio of cyclohexane to ethanol is 1:(2-3).
[0016] By adopting the above technical scheme, in the present application, by controlling the ratio of cyclohexane to ethanol, the dissolution of the high-density thioester antioxidant can be ensured while avoiding the introduction of too much high molecular weight polymer material into the sample solution to be tested, because the high molecular weight of the high molecular weight polymer material is large and too high a content thereof can easily clog the chromatographic column and reduce the service life of the chromatographic column.
[0017] Preferably, the concentration of the copper acetate in the cyclohexane and ethanol solution cannot be higher than 0.03 mg / mL.
[0018] By adopting the above technical solution, the content of copper acetate in this application should not be too high, as too high a concentration will affect the accuracy of the test.
[0019] Preferably, the heating temperature of the heated ultrasonic extraction is 60-65° C., and the heating ultrasonic extraction time is 20-40 min.
[0020] By adopting the above technical solution, the heating temperature is controlled to be lower than the boiling point of the solvent and lower than the melting point of the polymer in the present application, which can promote the dissolution of the polymer thioester antioxidant while only dissolving a small amount of the polymer, thereby improving the accuracy of the detection and avoiding the blockage of the chromatographic column. By controlling the extraction time, the polymer thioester antioxidant can be completely dissolved while reducing the dissolution of the polymer.
[0021] Preferably, in step S2, in order to ensure the accuracy of the detection, copper acetate also needs to be added to the standard solution, and the concentration of copper acetate in the standard needs to be the same as the concentration in the sample solution to be tested. The specific steps of adding copper acetate are as follows:
[0022] The copper acetate is used to prepare a copper acetate solution, and then the copper acetate solution is added to a volumetric flask containing a standard product according to a corresponding concentration ratio, and finally the volume is fixed to obtain a standard product solution; the solvent for preparing the standard product solution and the solvent for the copper acetate are cyclohexane and ethanol in the same volume ratio as that extracted in step S1.
[0023] By adopting the above technical scheme, in the present application, copper acetate is prepared into a solution and then mixed with a standard product, and finally the volume is fixed, so that insufficient dissolution of direct copper acetate can be avoided, and such an addition method can make copper acetate and the standard product better mixed and evenly mixed, so that the detection structure is more accurate. In the present application, copper acetate is added to the standard product solution, and the influence of adding copper acetate on the test absorption peak can also be avoided, thereby improving the accuracy of the test.
[0024] Preferably, in step S3, the chromatographic column of the liquid chromatography adopts a polypak Cyano chromatographic column with a specification of 250 mm in length, 4.6 mm in inner diameter and 5 um in film thickness.
[0025] Preferably, in step S3, during the liquid chromatography test, mobile phase A is dichloromethane, mobile phase B is n-hexane, and the volume ratio of mobile phase A to mobile phase B is (15-25):(75-80); the flow rate of the mobile phase is 0.5-1.5 ml / min, and the gas flow rate is 2.0-4.0 ml / min.
[0026] By adopting the above technical solution, in the present application, the proportion of the mobile phase, the flow rate of the mobile phase and the gas flow rate can better realize the detection of high molecular weight thioesters, and can further keep the detection cell clean and improve its detection accuracy.
[0027] Preferably, in step S3, the temperature of the evaporative light scattering detector is 40-60°C, and the column temperature of the chromatographic column is 30-50°C; during liquid chromatography detection, the injection volume is 20uL.
[0028] By adopting the above technical solution, the present application controls the detection conditions so that the content of the high molecular weight thioester antioxidant can be better detected, thereby improving the accuracy of the detection.
[0029] In summary, the present application includes at least one of the following beneficial technical effects:
[0030] 1. In view of the fact that macromolecular thioester antioxidants are insensitive to ultraviolet detectors, this application uses an evaporative light scattering detector to improve its detection effect. In addition, this application adjusts the detection conditions of liquid chromatography to further increase the sensitivity of its detection.
[0031] 2. In the present application, cyclohexane and ethanol are used to extract the polymer containing the high molecular weight thioester antioxidant, which can reduce the dissolution of the polymer and promote the dissolution of the high molecular weight thioester antioxidant, thereby improving the accuracy of the detection. In addition, copper acetate is further added to the solvent, and the adsorption of copper ions on sulfur elements can promote their further precipitation, thereby improving the accuracy of the test. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 High performance liquid chromatogram of the standard solution of antioxidant 412s tested in Example 1.
[0033] Figure 2 The standard curve and equation of the antioxidant 412s in Example 1.
[0034] Figure 3 High performance liquid chromatogram of the antioxidant 412s content in the polypropylene sample tested in Example 1.
[0035] Figure 4 High performance liquid chromatogram of the antioxidant 412s content in the polypropylene sample tested in Comparative Example 1.
[0036] Figure 5 High performance liquid chromatogram of the standard solution of the antioxidant DSTP tested in Example 2.
[0037] Figure 6 The standard curve and equation of the antioxidant DSTP in Example 2.
[0038] Figure 7 High performance liquid chromatogram of the antioxidant DSTP content in the polypropylene sample tested in Example 2. DETAILED DESCRIPTION
[0039] Example 1
[0040] The sample is a polypropylene product with 0.1% antioxidant 412s added.
[0041] Solution preparation:
[0042] Preparation of copper acetate solution: Dissolve 0.05064 g of copper acetate in a mixed solution of cyclohexane and ethanol in a volume ratio of 1:2. After dissolution is complete, transfer to a 500 mL volumetric flask and dilute to obtain a copper acetate solution with a concentration of approximately 0.1 mg / mL.
[0043] Preparation of standard solution: Weigh 0.05032 g of antioxidant 412s standard and dissolve it in a mixed solution of cyclohexane and ethanol in a volume ratio of 1:2. After complete dissolution, transfer it to a 250 mL volumetric flask and dilute to 250 mL to obtain a standard stock solution (approximately 0.2012 mg / mL).
[0044] 40mL, 20mL, 10mL, 5mL and 2.5mL of the standard stock solution were respectively taken and placed in 6 100mL volumetric flasks, and 10mL of copper acetate solution was added to each volumetric flask. After the volume was fixed to 100mL, a series of standard solutions with corresponding concentrations of (0.0805mg / mL, 0.0402mg / mL, 0.0201mg / mL, 0.0101mg / mL and 0.0050mg / mL) were obtained.
[0045] Preparation of sample solution to be tested:
[0046] 5 mL of the copper acetate solution was mixed with 45 mL of a mixed solution consisting of cyclohexane and ethanol in a volume ratio of 1:2 to obtain a mixed solution.
[0047] After the polypropylene product containing antioxidant 412s was crushed, 0.98467 g was weighed and added to the above mixed solution (50 mL). After sealing, it was placed at 60°C and ultrasonically extracted for 30 minutes. After the extraction was completed, it was centrifuged and the supernatant was taken as the sample solution to be tested.
[0048] The standard solution and the sample solution to be tested were tested by high performance liquid chromatography (wherein, the evaporative light detector model: Tongwei, UM5000), and the test conditions were as follows:
[0049] The HPLC column used was a polypak Cyano column with a length of 250 mm, an inner diameter of 4.6 mm, and a film thickness of 5 μm.
[0050] Mobile phase A was dichloromethane, mobile phase B was n-hexane, and the volume ratio of mobile phase A to mobile phase B was 20:80; the flow rate of the mobile phase was 1.0 ml / min, and the gas flow rate was 3.0 ml / min.
[0051] The detection temperature of the evaporative light scattering detector was 50°C, the column temperature of the chromatographic column was 40°C, and the injection volume was 20uL.
[0052] Each sample was tested 3 times during the test, and the HPLC spectrum of the standard curve (0.0402 mg / mL) was as follows Figure 1 The standard curve is shown in Figure 2 shown; from Figure 1 It can be seen that its single characteristic absorption peak in HPLC has a high linear correlation from the standard curve equation.
[0053] The sample to be tested is subjected to liquid phase testing, and the results are as follows Figure 3 As shown, from Figure 3 It can be seen that in addition to the characteristic absorption peak of antioxidant 412s, there are many other impurity peaks, which may be other impurities in polypropylene. According to the peak area, the concentration of antioxidant 412s in the sample to be tested is calculated to be 0.0193 mg / mL. By calculation, it can be concluded that its content is 0.0982%, which is very different from the known content, indicating that the antioxidant in polypropylene has been basically completely dissolved. The method in this application can accurately test polymers.
[0054] Comparative Example 1
[0055] The method is basically the same as Example 1, except that the processing method of the sample to be tested is different, as follows:
[0056] After the polypropylene product containing antioxidant 412s was crushed, 0.99164 g was weighed and added to a mixed solution (45 mL) of n-hexane and ethanol in a volume ratio of 1:2. After sealing, it was placed at 60°C and ultrasonically extracted for 30 minutes. After the extraction was completed, 5 mL of copper acetate solution was added, centrifuged, and the supernatant was taken as the sample solution to be tested. The measured HPLC chromatogram is shown as follows: Figure 4 As shown, the concentration was calculated based on the peak area to be 0.0181 mg / mL, and the content was calculated to be 0.0913%, which is quite different from the known content, indicating that the addition of copper acetate can significantly promote the extraction of antioxidant 412s.
[0057] Example 2
[0058] The sample is a polypropylene product with 0.15% antioxidant DSTP added.
[0059] Solution preparation:
[0060] Preparation of copper acetate solution: Dissolve 0.04985 g of copper acetate in a mixed solution of cyclohexane and ethanol in a volume ratio of 1:2. After dissolution is complete, transfer to a 500 mL volumetric flask and dilute to obtain a copper acetate solution with a concentration of approximately 0.1 mg / mL. Preparation of standard solution: Weigh 0.05101 g of the antioxidant DSTP standard and dissolve it in a mixed solution of cyclohexane and ethanol in a volume ratio of 1:2. After complete dissolution, transfer to a 250 mL volumetric flask and dilute to 250 mL to obtain a standard mother solution (approximately 0.2040 mg / mL).
[0061] 40mL, 20mL, 10mL, 5mL and 2.5mL of the standard stock solution were respectively taken and placed in 6 100mL volumetric flasks, and 10mL of copper acetate solution was added to each volumetric flask. After the volume was fixed to 100mL, a series of standard solutions with corresponding concentrations of (0.0816mg / mL, 0.0408mg / mL, 0.0204mg / mL, 0.0102mg / mL and 0.0051mg / mL) were obtained.
[0062] Preparation of sample solution to be tested:
[0063] 5 mL of the copper acetate solution was mixed with 45 mL of a mixed solution consisting of cyclohexane and ethanol in a volume ratio of 1:2 to obtain a mixed solution.
[0064] After the polypropylene product containing the antioxidant DSTP was crushed, 0.99964 g was weighed and added to the above mixed solution (50 mL). After sealing, it was placed at 65°C and ultrasonically extracted for 30 minutes. After the extraction was completed, it was centrifuged and the supernatant was taken as the sample solution to be tested.
[0065] The standard solution and the sample solution to be tested were tested by HPLC respectively, and the test conditions were as follows:
[0066] The standard solution and the sample solution to be tested were tested by high performance liquid chromatography (wherein, the evaporative light detector model: Tongwei, UM5000), and the test conditions were as follows:
[0067] The HPLC column used was a polypak Cyano column with a length of 250 mm, an inner diameter of 4.6 mm, and a film thickness of 5 μm.
[0068] Mobile phase A was dichloromethane, mobile phase B was n-hexane, and the volume ratio of mobile phase A to mobile phase B was 20:80; the flow rate of the mobile phase was 1.0 ml / min, and the gas flow rate was 3.0 ml / min.
[0069] The detection temperature of the evaporative light scattering detector was 50°C, the column temperature of the chromatographic column was 40°C, and the injection volume was 20uL.
[0070] Each sample was tested 3 times during the test, and the HPLC spectrum of the standard curve (0.0408 mg / mL) was as follows Figure 5 The standard curve is shown in Figure 6 shown; from Figure 5 It can be seen that its single characteristic absorption peak in HPLC has a high linear correlation from the standard curve equation.
[0071] The sample to be tested is subjected to liquid phase testing, and the results are as follows Figure 7 As shown, from Figure 7 It can be seen that in addition to the characteristic absorption peak of the antioxidant DSTP, there are three other impurity peaks, which may be other impurities in polypropylene. According to the peak area, the concentration of the antioxidant DSTP in the sample to be tested is calculated to be 0.0293 mg / mL. By calculation, it can be concluded that its content is 0.1466%, which is very different from the known content, indicating that the antioxidant DSTP in the polypropylene has been basically completely dissolved. The method in this application can accurately test the antioxidant DSTP in the polymer.
[0072] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A method for detecting the content of a thioester antioxidant, comprising the following steps: S1. Sample pretreatment: crush the sample to be tested and extract it to obtain the sample solution to be tested; S2. Prepare standard solution: prepare a standard solution of thioester antioxidant, the solvent in the standard solution needs to be the same as the solvent used to extract the sample in step S1; S3, testing: the standard solution in step S2 is sequentially subjected to liquid chromatography testing to obtain a standard curve, and then the sample solution to be tested in step S1 is subjected to liquid chromatography testing, and the corresponding concentration is calculated according to the test results and the standard curve; the liquid chromatography uses an evaporative light scattering detector; In step S1, the specific steps of extraction are: accurately weighing the crushed sample to be tested, adding it to a mixed solvent composed of cyclohexane and ethanol, and adding copper acetate to the solvent, performing heating and ultrasonic extraction, and after the extraction is completed, centrifuging, and absorbing the supernatant as the sample solution to be tested, wherein the sample to be tested is a polyolefin product containing antioxidant 412s or antioxidant DSTP; In step S3, during the liquid chromatography test, the liquid chromatography column uses a polypak Cyano column, the mobile phase A is dichloromethane, the mobile phase B is n-hexane, and the volume ratio of the mobile phase A to the mobile phase B is (20-25):(75-80).
2. The method for detecting the content of thioester antioxidant according to claim 1, characterized in that: The volume ratio of cyclohexane to ethanol is 1:(2-3).
3. The method for detecting the content of thioester antioxidant according to claim 1, characterized in that: The concentration of the copper acetate in the cyclohexane and ethanol solution cannot be higher than 0.03 mg / mL.
4. The method for detecting the content of thioester antioxidant according to claim 1, characterized in that: The heating temperature of the heated ultrasonic extraction is 60-65° C., and the heating ultrasonic extraction time is 20-40 minutes.
5. The method for detecting the content of thioester antioxidant according to claim 1, characterized in that: In step S2, in order to ensure the accuracy of the detection, copper acetate also needs to be added to the standard solution, and the concentration of copper acetate in the standard needs to be the same as the concentration in the sample solution to be tested. The specific steps of adding copper acetate are: preparing a copper acetate solution with copper acetate, and then adding the copper acetate solution to a volumetric flask containing the standard according to a corresponding concentration ratio, and finally fixing the volume to obtain a standard solution; the solvent of the standard solution and the solvent of copper acetate adopt cyclohexane and ethanol with the same volume ratio as that extracted in step S1.
6. The method for detecting the content of thioester antioxidant according to claim 1, characterized in that: In step S3, the specifications of the chromatographic column are 250 mm in length, 4.6 mm in inner diameter, and 5 microns in film thickness.
7. The method for detecting the content of thioester antioxidant according to claim 1, characterized in that: In step S3, during the liquid chromatography test, the flow rate of the mobile phase is 0.5-1.5 ml / min, and the gas flow rate is 2.0-4.0 ml / min.
8. The method for detecting the content of thioester antioxidant according to claim 1, characterized in that: In step S3, the temperature of the evaporative light scattering detector is 40-60°C, and the column temperature of the chromatographic column is 30-50°C.